Heparins and Venous Thromboembolism: Current Practice and Future Directions - Prandoni, Paolo (Thrombosis and Haemostasis, 2001)
Unfractionated heparin (UFH) in adjusted doses and low-molecularweight heparins (LMWH) in fixed doses are the chosen therapy for the initial treatment of venous thromboembolism. The use of UFH protocols ensures that virtually all patients will promptly achieve the therapeutic range for the activated partial thromboplastin time. However, proper use of UFH requires considerable expertise, can cause inconvenience and has limitations. Unmonitored therapy with subcutaneous LMWH is at least as effective and safe as adjusted-dose UFH, is associated with a considerable reduction of mortality in cancer patients, and permits the treatment of suitable patients in an outpatient setting.LMWH in high prophylactic doses is more effective than UFH and oral anticoagulants for prevention of postoperative venous thrombosis in major orthopedic surgery. Whether thromboprophylaxis should be continued for a few additional weeks after hospital discharge is controversial. LMWH and UFH are equally effective for prevention of postoperative deep-vein thrombosis in cancer patients. In a recent controlled randomized trial, enoxaparin in high prophylactic doses was an effective and safe measure of thromboprophylaxis in ordinary bedridden patients.The efficacy and safety of pentasaccharide (the smallest antithrombin binding sequence of heparin) in the treatment and prevention of venous thromboembolic disorders is currently under investigation.
Keywords: Unfractionated heparin; low-molecular-weight heparin; deep-vein thrombosis; pulmonary embolism; pentasaccharide